2006
DOI: 10.1017/s1047951106000357
|View full text |Cite
|
Sign up to set email alerts
|

An index for evaluating results in paediatric cardiac intensive care

Abstract: We found that surgery undertaken in the neonatal period, weight below the 5th percentile, the presence of associated clinical risk factors, operations of higher complexity, and more than 90 minutes of cardiopulmonary bypass were all significantly associated with mortality. Our suggested new index showed a linear correlation with mortality, and in our current experience, has proved a valuable tool for predicting adverse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…The good surgical outcome was reinforced by the clinicalsurgical index, more recently, proposed in Brazil [15], whose scores (5.5 vs. 5) correspond to risks of death from 11.70% to 23.98%, due mainly to the prevalence of low body weight, indicative of malnutrition, and genetic syndromes, pulmonary hypertension and congestive heart failure, which certainly influenced the morbidity. These similar indices and scores of the operated groups confirm the homogeneity needed for analysis, highlighting the variability in the weights, which are incompatible with regard to age, especially due to the nutritional changes resulting from heart diseases.…”
Section: Fig 6 -Il-6/il10 Proportion In the Aprotinin And Control Grmentioning
confidence: 99%
See 2 more Smart Citations
“…The good surgical outcome was reinforced by the clinicalsurgical index, more recently, proposed in Brazil [15], whose scores (5.5 vs. 5) correspond to risks of death from 11.70% to 23.98%, due mainly to the prevalence of low body weight, indicative of malnutrition, and genetic syndromes, pulmonary hypertension and congestive heart failure, which certainly influenced the morbidity. These similar indices and scores of the operated groups confirm the homogeneity needed for analysis, highlighting the variability in the weights, which are incompatible with regard to age, especially due to the nutritional changes resulting from heart diseases.…”
Section: Fig 6 -Il-6/il10 Proportion In the Aprotinin And Control Grmentioning
confidence: 99%
“…Retrospectively, we calculated the index recently proposed by Mattos et al [15] in 2006. The times of use of inotropic and EV vasoactive drugs, time of use of nitric oxide, and duration of stay in PICU in adittion to the elapsed until discharge or death were measured, as well as the duration of mechanical ventilation (MV).…”
Section: Postoperative Clinical Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrospectively, we calculated the index recently proposed by Mattos et al [3] in 2006. The times of use of inotropes, IV vasoactive drugs, nitric oxide, and stay in the PICU and elapsed time until discharge or death were measured as well as the duration of mechanical ventilation (MV)…”
Section: Postoperative Clinical Conditionsmentioning
confidence: 99%
“…Strategies to anticipate them, avoid them or fight them are of intense interest, especially the preoperative scores of risk stratification, the anesthetic and surgical refinement, and the optimization of CPB circuits. The use of Aprotinin (Trasylol®, Bayer Pharmaceuticals Corporation), a nonspecific serine proteases inhibitor, consisting of the polypeptide chain of 6512 Daltons, hydrophilic and basic, was one of these pharmacological strategies, whose hemostatic property reduces blood loss after cardiopulmonary bypass procedure [1][2][3]. Recently, in 2006, Arnold et al [4], in a meta-analysis of 12 randomized studies involving 612 children undergoing CPB, observed, with Aprotinin, 33% reduction in the rate of transfusion.…”
Section: Introductionmentioning
confidence: 99%